EVALUASI PENGGUNAAN BUKU KESEHATAN IBU ANAK, KARTU IBU, REGISTER ANC DI PUSKESMAS - Herinawati Herinawati; Sri Yun Utama; Atika Fadhilah Danaz Nst; Nuraida Nuraida; Iksaruddin Iksaruddin (Poltekkes Kemenkes Jambi, 2021)
Background: Maternal and child health services including immunization, disease records and child development problems must be recorded completely and correctly. The MCH Handbook is useful for monitoring maternal and child health. The use of maternal and child health services is still constrained by the lack of synchronization between the MCH books that the mother will bring home, and the mother's card that is archived at the puskesmas so that there are several points of information in the MCH book that are not on the mother's card so that it will be difficult to find data and make a report. Methods: This study used a PICOS review literature study method with 7 articles using the PRISMA approach. The objective of this study was to determine the evaluation of the use of the MCH booklet, mother card, and ANC register at the health center. Using the keywords